Level Of Satisfaction Among Graduates (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the level of satisfaction among graduate students at Eastern Visayas State University-Ormoc Campus in Ormoc City. . About 231 students are selected as samples using convenience sampling. The data is collected by the use of a survey questionnaire and analyzed using SPSS software. The findings reveal that students have a high level of satisfaction on Personal and Professional factors, and a moderate level of satisfaction on Student Support and Instruction-related factors. The younger group of both males and females enrolled in Education and Technology programs has a higher level of satisfaction than the older group enrolled in Engineering, which has a moderate level of satisfaction. There is no significant difference in personal and professional satisfaction levels by gender and age, but there is a significant difference by program. When compared to Technology and Engineering students, Education students are more satisfied. The relationship between variables is found to be moderately significant.